2021
DOI: 10.3389/fpls.2021.667539
|View full text |Cite
|
Sign up to set email alerts
|

Double-Stranded RNA Targeting Dicer-Like Genes Compromises the Pathogenicity of Plasmopara viticola on Grapevine

Abstract: Downy mildew caused by Plasmopara viticola is one of the most devastating diseases of grapevine, attacking all green parts of the plant. The damage is severe when the infection at flowering stage is left uncontrolled. P. viticola management consumes a significant amount of classical pesticides applied in vineyards, requiring efficient and environmentally safe disease management options. Spray-induced gene silencing (SIGS), through the application of exogenous double-stranded RNA (dsRNA), has shown promising re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 29 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…They reported that antisense sRNAs targeting the Hpa-CesA3 gene in Emoy2 and Cala2 isolates inhibited spore germination and thus infection of Arabidopsis , while sense sRNAs had no obvious effect on Hpa pathogenicity. When Haile et al (2021) used dsRNA targeting the DCL1 and DCL2 genes in grapevine downy mildew pathogen Plasmopara viticola , they observed reduction in the expression level of these genes as well as in the disease progress rate in the already established infection. Similar SIGS studies with dsRNA against the late blight pathogen P. infestans has been carried out by Kalyandurg et al (2021) .…”
Section: Host-induced Gene Silencing and Spray-induced Gene Silencing...mentioning
confidence: 99%
“…They reported that antisense sRNAs targeting the Hpa-CesA3 gene in Emoy2 and Cala2 isolates inhibited spore germination and thus infection of Arabidopsis , while sense sRNAs had no obvious effect on Hpa pathogenicity. When Haile et al (2021) used dsRNA targeting the DCL1 and DCL2 genes in grapevine downy mildew pathogen Plasmopara viticola , they observed reduction in the expression level of these genes as well as in the disease progress rate in the already established infection. Similar SIGS studies with dsRNA against the late blight pathogen P. infestans has been carried out by Kalyandurg et al (2021) .…”
Section: Host-induced Gene Silencing and Spray-induced Gene Silencing...mentioning
confidence: 99%
“…Studies in other organismal interactions have demonstrated other microbes/pathogens, including plant fungal pathogens Fusarium oxysporum 18 and Verticillium dahliae 7 , an oomycete pathogen H. arabidopsidis 16 , an animal fungal pathogen Beauveria bassiana of mosqiuito 17 , a bacterial pathogen 19 and even symbiotic microbes, such as ectomycorrhizal fungus Pisolithus microcarpus 20 and Rhizobium (Bradyrhizobium japonicum) 21 , also utilize host Argonaute proteins for crosskingdom RNAi. The biogenesis of these pathogen sRNAs involved in cross-kingdom RNAi are also largely dependent on pathogen DCL proteins [7][8]10,15,[22][23][24][25][26] . These studies demonstrate crosskingdom RNAi is a conserved mechanism across different species, including plant and animal hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Grape breeding programs aiming at the introgression of resistance traits from wild species to cultivated varieties have the limit to lose trait specificity of clones identified in important vine cultivars. Target sequences coding for Dicer and Dicer-like ( DCL) proteins have been identified as crucial genes for the pathogenicity of B. cinerea and P. viticola and used in SIGS approaches to control these two severe pathogens (Wang et al, 2016 ; Capriotti et al, 2020 ; Haile et al, 2021 ). A SIGS approach against the oomycete P. viticola was shown to work effectively both as preventive and therapeutic treatment (Haile et al, 2021 ).…”
mentioning
confidence: 99%
“…Target sequences coding for Dicer and Dicer-like ( DCL) proteins have been identified as crucial genes for the pathogenicity of B. cinerea and P. viticola and used in SIGS approaches to control these two severe pathogens (Wang et al, 2016 ; Capriotti et al, 2020 ; Haile et al, 2021 ). A SIGS approach against the oomycete P. viticola was shown to work effectively both as preventive and therapeutic treatment (Haile et al, 2021 ). A different approach for downy mildew control is presented by Marcianò et al ( 2021 ) who silenced a grapevine susceptibility gene by exogenous dsRNA application, resulting in reduced disease severity after artificial P. viticola inoculation.…”
mentioning
confidence: 99%